Effect of Work Discipline and Performance Advantages on Personnel Performance in Polda Jatim with Motivation as an Intervening Variable - Nyenyep Mudiarti; Pompong Budi Setiadi; Sri Rahayu (Budapest International Research and Critics University, 2022)
Securing National Vital Objects is the main task of the Ditpamobvit personnel of the East Java Police. In carrying out these tasks so that the given performance is maximal, it is necessary to have high work motivation. Work discipline and work benefits are things that affect one's work motivation in order to improve the given performance. This study aims to determine the effect of work discipline and performance allowances on the performance of Ditpamobvit personnel of the East Java Regional Police with motivation as an intermediary variable. The research method is literature review through Google Scholar and Science Direct to get journals with a span of the last 5 years (2017-2022). The collected journal data is then analyzed and presented as a table of literature review results. The results of the research analysis obtained 11 articles that are relevant to the topic of this research. The obtained articles explain that work discipline significantly affects work motivation, performance allowances affect work motivation, and work motivation jointly. Work discipline through work motivation indirectly affects personnel performance and explains that performance allowances indirectly affect employee performance of work motivation. Discipline and performance allowances indirectly affect motivation.